2020
DOI: 10.4108/eai.31-1-2020.162831
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Power Transfer Near-field Technologies for Unmanned Aerial Vehicles (UAVs): A Review

Abstract: Wireless power transfer (WPT) techniques are being popular currently with the development of midrange wireless powering and charging technology to gradually substitute the need for wired devices during charging. Unmanned Aerial Vehicles (UAVs) are also being used with many practical purposes for agriculture, surveillance, and healthcare, etc. There is a trade-off between the weight of the UAVs or their batteries and their flying time. In order to support those UAVs perform better in their tasks, WPT is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 88 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…The authors addressed the benefits and drawbacks of available charging techniques; however, they concluded that in-detail studies have to be conducted to increase flight time. Anh M. Le et al [59] reviewed near field charging techniques for UAV in the aspect of transfer power, transfer efficiency and charging distance. The authors also provided an overview of challenges and opportunities in near field transmission, which summarized that mid-range charging techniques such as IPT could increase the range of UAVs.…”
Section: Existing Surveysmentioning
confidence: 99%
“…The authors addressed the benefits and drawbacks of available charging techniques; however, they concluded that in-detail studies have to be conducted to increase flight time. Anh M. Le et al [59] reviewed near field charging techniques for UAV in the aspect of transfer power, transfer efficiency and charging distance. The authors also provided an overview of challenges and opportunities in near field transmission, which summarized that mid-range charging techniques such as IPT could increase the range of UAVs.…”
Section: Existing Surveysmentioning
confidence: 99%
“…Depending on the antenna size, transmitting power and the propagation environment, and radiative (i.e., electromagnetic) frequency, WPT using concurrent omnidirectional power delivery to multiple receivers requiring smaller transmitter/receiver may achieve power delivery over distances varying from a few meters to even hundreds of kilometres. These features make aforementioned WPT approaches suitable for the use of UAV environment compared to the near-field inductive coupling WPT with a range of up to several centimetres and magnetic resonant (MR) WPT with a range up to several meters where the transmitter and receiver need to be in close proximity [43], [46], [47]. More explicitly, radio frequency (RF) transmission enabled WPT is a promising solution to provide perpetual and cost-effective energy supplies to low-power electronic devices, and it is anticipated to have abundant applications spanning from lowpower wireless charging for devices such as radio frequency identification (RFID) tags, wireless sensors, IoT, and consumer electronics (smartphones, laptops, household robots, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…Recent developments in power electronics in reference to switching devices have made an impact in the field of wireless power charging, which has evolved its concept from low power to high power applications because of its safe, reliable, and convenient charging techniques. Especially, after the success of wireless mobile charging in the present market, the topics related to wireless power transfer (WPT) have expanded to medical [1][2][3], automobile [4][5][6][7], and automation areas [8][9][10][11][12][13]. In the past decade, inductive wireless power transfer (IPT) and resonant wireless power transfer have drawn tremendous attention in both industry and academic fields.…”
Section: Introductionmentioning
confidence: 99%